EVI5 is a risk gene for multiple sclerosis. - Hoppenbrouwers, I; Aulchenko, Y; Ebers, G; Ramagopalan, S; Oostra, B; van Duijn, C; Hintzen, R (2008)
HLA-DRB1 is the major locus associated with risk for multiple sclerosis (MS). A recent genome-wide study showed three additional single-nucleotide polymorphisms (SNPs), within the IL2RA and IL7RA genes respectively, also to be associated with MS. Consistent association but lower significance was found for 13 other SNPs. In this study, we aimed to verify association of these SNPs with MS in 46 MS patients and 194 controls from a Dutch genetically isolated population. Apart from the human leukocyte antigen locus, the EVI5 gene on chromosome 1 was confirmed as a novel risk gene, with odds ratios (ORs) even higher than those from the MS Consortium (ORs 2.01 and 1.9; P=0.01). The risk effect of EVI5 was further validated for the general MS population in an independent set of 1318 MS patients from the Canadian Collaborative Project on the Genetic Susceptibility to MS. On the basis of the transmission disequilibrium testing, a weak but significant risk effect was observed (OR 1.15; P=0.03 and OR 1.15; P=0.04). This study confirms EVI5 as another risk locus for MS; however, much of the genetic basis of MS remains unidentified.